Analysing the financial innovation-based characteristics of stock market efficiency using fuzzy decision-making technique - Dadan Rahadian; Anisah Firli; Hasan Dinçer; Serhat Yüksel; Alexey Mikhaylov (Financial Innovation)
Abstract Necessary actions should be taken to ensure stock market efficiency; thus, financial innovation-based criteria that affect stock market efficiency should be improved. However, simultaneously improving all criteria is difficult; therefore, performing priority analysis is important for carrying out this process effectively and efficiently. Accordingly, this study aims to evaluate the financial innovation-based characteristics of stock market efficiency. This study’s main research question within this framework is identifying which factors should be prioritized to improve the stock market. In this scope, we created a novel fuzzy decision-making model consisting of two stages. First, selected criteria for the financial innovation-based characteristics of stock market efficiency are weighted. In this process, quantum spherical fuzzy sets based on DEMATEL are considered. In the second stage, selected economies are ranked using the technique for order of preference by similarity to ideal solution (TOPSIS) approach. This study’s main contribution is that the DEMATEL technique in calculating criterion weights in the decision-making analysis process provides some advantages. With the help of this situation, the causal directions between these items can be considered; thus, it is possible to determine the most accurate strategies. The findings demonstrate that providing tax advantages is the most important factor in ensuring stock market efficiency. Moreover, the excellence of the financial system is critical in ensuring stock market efficiency. In this context, it is possible to provide tax advantages, especially for long-term investments. Thus, long-term investments can be increased, significantly increasing the market’s stability.